The effect of a dietary training special program on improving functional situation and achievement in terms of muscular fatigue and some functional indicators for the men runners of (1500) meters race - Bahri Shamkhi Hussein, Ghassan; Qasim Muhammad Ibrahim, Atheer; Ataallah Essa Alobayde, Waleed (International Journal of Psychosocial Rehabilitation, 2020)
By following the researchers to intermediate jogging, including runners who ran 1500 meters in the exercise of official racing for some clubs Iraq noted that there is a decrease in the level of achievement researchers believe to be caused by the decline in the functional and physical susceptibility of most runners as well as the lack of adaptations that are functional and positive for body organs despite undergoing hostility to training programs for a variety of delays, fatigue, and completing the race in less time with more effort and also runners not subject to effective nutritional or nutrition programs consistent with the nature of the effort exerted during training and competition. Researcher Wen believes that the research problem It is manifested in the fact that most of the trainers do not rely on some functional indicators in addition to the heart rate with the help of specialists and their adoption as an indicator of the development of the functional and physical level. The researcher thus assumed the existence of statistically significant differences between the pre-test and the post-test of the muscle fatigue index and the values of the functional indicators and achievement of the research sample. The results obtained by the researcher in the tribal and dimensionality tests that the researcher found a group of the most important conclusions that the index of muscle fatigue has a major role in the preparation of training programs for the development of the functional ability of the players and the legalization of the training load must be adopted by the trainers as well as an improvement of the functional state of the runners through Most of the studied functional indicators have improved between pre- and post-testing for the studied research sample, and among the recommendations is the adoption of effective and appropriate food programs in line with the physical effort of the runners and the various activities.